Genetic diversity and symbiotic effectiveness of Bradyrhizobium strains nodulating selected annual grain legumes growing in Ethiopia - Degefu, T.; Woldemeskel, Endalkachew; Rasche, F. (Microbiology Society, 2018)
Vigna unguiculata, Vigna radiata and Arachis hypogaea growing in Ethiopia are nodulated by a genetically diverse group of Bradyrhizobium strains. To determine the genetic identity and symbiotic effectiveness of these bacteria, a collection of 36 test strains originating from the root nodules of the three hosts was investigated using multilocus sequence analyses (MLSA) of core genes including 16S rRNA, recA, glnII, gyrB, atpD and dnaK. Sequence analysis of nodA and nifH genes along with tests for symbiotic effectiveness using δ15N analysis were also carried out. The phylogenetic trees derived from the MLSA grouped most test strains into four well-supported distinct positions designated as genospecies I–IV. The maximum likelihood (ML) tree that was constructed based on the nodA gene sequences separated the entire test strains into two lineages, where the majority of the test strains were clustered on one of a well-supported large branch that comprise Bradyrhizobium species from the tropics. This clearly suggested the monophyletic origin of the nodA genes within the bradyrhizobia of tropical origin. The δ15N-based symbiotic effectiveness test of seven selected strains revealed that strains GN100 (δ15 N=0.73) and GN102 (δ15 N=0.79) were highly effective nitrogen fixers when inoculated to cowpea, thus can be considered as inoculants in cowpea production. It was concluded that Ethiopian soils are a hotspot for rhizobial diversity. This calls for further research to unravel as yet unknown bradyrhizobia nodulating legume host species growing in the country. In this respect, prospective research should also address the mechanisms of symbiotic specificity that could lead to high nitrogen fixation in target legumes.